Demonstrasi Pemanfaatan Etanol Menjadi Hand Sanitizer dan Spray Anti Nyamuk Pada Kelompok PKK Desa Ngombakan Kecamatan Polokarto Kabupaten Sukoharjo - Zakaria, Salsabila Anggraini; Amaria, Meilani; Collin, Alessandro Inouva; Sumartiningsih, Sri; Efendi, Daryono (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The Community Service Program conducted by the GIAT 13 UNNES students in Ngombakan Village, Polokarto District, Sukoharjo Regency aimed to utilize local natural resources through the development of two innovative hygiene products, namely ETNOS Hand Sanitizer and ETNOS Anti-Mosquito Spray. This program was driven by the community’s need for safe, affordable, and environmentally friendly health products. The activities were carried out through several stages, including preparation, dissemination of scientific material, demonstrations, and hands-on practice involving members of the PKK women’s group. Participants were trained to process local ethanol and lemongrass through boiling, formulation, mixing techniques, and safe product packaging. The results showed that participants were able to produce high-quality hand sanitizer and anti-mosquito spray with strong natural aromas and noticeable effectiveness. The program also enhanced community understanding of local resource utilization and encouraged self-reliance in meeting household hygiene needs.